2017
DOI: 10.3390/v9070166
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Propagation of a Fluorescent Infectious Clone of a Polerovirus Following Inoculation by Agrobacteria and Aphids

Abstract: A fluorescent viral clone of the polerovirus Turnip yellows virus (TuYV) was engineered by introducing the Enhanced Green Fluorescent Protein (EGFP) sequence into the non-structural domain sequence of the readthrough protein, a minor capsid protein. The resulting recombinant virus, referred to as TuYV-RTGFP, was infectious in several plant species when delivered by agroinoculation and invaded efficiently non-inoculated leaves. As expected for poleroviruses, which infect only phloem cells, the fluorescence emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…A second possible Ce pathway is based on previous studies involving the transport of particles through the gut wall to the hemocoel, which commonly occurs with viruses (Brault et al 2007;Tamborindeguy et al 2010). Although most of the aphid-transmitted plant viruses are 20 to 25 nm wide (Sicard et al 2015;Boissinot et al 2017), which is about one-tenth the diam of nano-CeO 2 clusters, this transport is performed by transcytosis (endocytosis/exocytosis) (Seddas et al 2004), and involves specific receptors. In this respect, nano-CeO 2 could cause histological changes in the tissues of M. persicae, similar to what was reported in a study performed with the worm Eisenia fetida (Savigny) (Annelida: Lumbricidae) (Lahive et al 2014), resulting in absorption and transport.…”
Section: Discussionmentioning
confidence: 99%
“…A second possible Ce pathway is based on previous studies involving the transport of particles through the gut wall to the hemocoel, which commonly occurs with viruses (Brault et al 2007;Tamborindeguy et al 2010). Although most of the aphid-transmitted plant viruses are 20 to 25 nm wide (Sicard et al 2015;Boissinot et al 2017), which is about one-tenth the diam of nano-CeO 2 clusters, this transport is performed by transcytosis (endocytosis/exocytosis) (Seddas et al 2004), and involves specific receptors. In this respect, nano-CeO 2 could cause histological changes in the tissues of M. persicae, similar to what was reported in a study performed with the worm Eisenia fetida (Savigny) (Annelida: Lumbricidae) (Lahive et al 2014), resulting in absorption and transport.…”
Section: Discussionmentioning
confidence: 99%
“…Veins from the upper leaves of infected plants were collected with an adhesive tape following a published protocol [25]. The veins were then fixed overnight at 4 • C under gentle stirring in embryo dishes containing 4% paraformaldehyde (PFA) and 0.2% Triton X-100 diluted in phosphate-buffered saline 1X pH 7.4 (PBS).…”
Section: Plant and Insect Dissectionsmentioning
confidence: 99%
“…Since stable virions are required for TuYV systemic spread in Nicotiana species ( Brault et al, 2003 ) and in A. thaliana plants ( Hipper et al, 2014 ), the genome size constraint imposed for the formation of stable isometric particles was taken into consideration in the design of the TuYV-based VIGS vectors. Previous studies have shown that inserting long foreign sequences in the genome of poleroviruses could be detrimental to genome stability, systemic movement or aphid transmission of the resulting viruses ( Nurkiyanova et al, 2000 ; Boissinot et al, 2017 ). In particular the genome integrity of TuYV was seriously affected in A. thaliana ( Boissinot et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that inserting long foreign sequences in the genome of poleroviruses could be detrimental to genome stability, systemic movement or aphid transmission of the resulting viruses ( Nurkiyanova et al, 2000 ; Boissinot et al, 2017 ). In particular the genome integrity of TuYV was seriously affected in A. thaliana ( Boissinot et al, 2017 ). Furthermore most of the viral proteins encoded by TuYV are required to establish an efficient systemic proliferation and promote aphid transmission ( Brault et al, 1995 ; Ziegler-Graff et al, 1996 ; Bruyère et al, 1997 ; Rodriguez-Medina et al, 2015 ; Smirnova et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation